Contribution of Tocols to Food Sensorial Properties, Stability, and Overall Quality. (3rd December 2020) - Delgado, Amélia; Al-Hamimi, Said; Ramadan, Mohamed Fawzy; Wit, Maryna De; Durazzo, Alessandra; Nyam, Kar Lin; Issaoui, Manel
Abstract : This paper reviews the contribution of tocopherols and tocotrienols (tocols) to food quality as well as their bioactivity and health-promoting properties, which have attracted researchers and food technologists. Tocols are lipophilic phenolic antioxidants encompassing tocopherols that are characterized by a saturated side chain and tocotrienols with an unsaturated isoprenoid side chain. Tocols are natural constituents of several foods like dairy, vegetable oils, nuts, and grains. Their presence in foods, namely, as food additives, helps prevent lipid oxidation, which negatively affects the sensorial quality of foods, and even the nutritional value and safety. Supplementation of animals' diets with tocopherols has proven its effectiveness in preserving fresh color and flavor of the meat. Although alfa-tocopherol displays much higher vitamin E activity than other tocols, health outcomes have been reported for tocotrienols, thus calling for more studies.